2014
DOI: 10.1093/hsw/hlu018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between School-Based Health Center Use, School Connection, and Academic Performance

Abstract: School-based health centers (SBHCs) benefit the overall health of underserved communities. In fact, there is an abundance of evidence suggesting the positive effects that SBHCs have on physical and mental health. However, research related to understanding the relationship of SBHCs to academic outcomes such as performance and school connectedness is sparse. The purpose of the current study was to (a) compare differences between elementary, middle, and high school student SBHC users and nonusers on school connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 31 publications
4
51
0
Order By: Relevance
“…Five studies 46,70,76,78,90 reported that a median of 69% (IQI=61%, 82%) of students who enrolled in SBHCs received services. Across 15 studies, 54,56,59,62,68,71,73,79,84,8688,91,92,96 a median of 52% (IQI=38%, 61%) of students in schools with SBHCs used the clinics. A summary of evidence from included studies is available on the Community Guide website (www.thecommunityguide.org/healthequity/education/supportingmaterials/SET-schoolbasedhealthcenters.pdf).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies 46,70,76,78,90 reported that a median of 69% (IQI=61%, 82%) of students who enrolled in SBHCs received services. Across 15 studies, 54,56,59,62,68,71,73,79,84,8688,91,92,96 a median of 52% (IQI=38%, 61%) of students in schools with SBHCs used the clinics. A summary of evidence from included studies is available on the Community Guide website (www.thecommunityguide.org/healthequity/education/supportingmaterials/SET-schoolbasedhealthcenters.pdf).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Seventeen studies in 18 papers 4649,56,6569,74,78,85,88,89,91,92,94 assessed SBHC user–only effects by comparing users with non-users within SBHC schools (eight studies 46,68,69,78,88,91,92,94 ) or SBHC users with users of healthcare sources in non-SBHC settings (nine studies in ten papers 4749,56,6567,74,85,89 ). Four studies 59,76,78,90 assessed both whole-school and SBHC user–only effects.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…SBHCs have been shown to increase access to and utilization of high-quality cost-effective health care services for children and adolescents, especially in underserved populations (Anyon et al, 2013;Bains, Franzen, & White-Frese, 2014;Guo et al, 2005;Soleimanpour, Geierstanger, Kaller, McCarter, & Brindis, 2010;Wade et al, 2008). Although school success is influenced by multiple factors, when comparing students who use an SBHC to those who do not, several studies have found an association between SBHC use and improved school connection, increased academic scores, increased school attendance, and decreased school dropout (Kerns et al, 2011;Strolin-Goltzman, 2010;Strolin-Goltzman, Sisselman, Melekis, & Auerbach, 2014;Van Cura, 2010;Walker, Kerns, Lyon, Bruns, & Cosgrove, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Peter et al School attachment 1 has long been recognized as an important attribute for youth to possess within a school climate. Studies suggest that feeling a close attachment to school is associated with higher academic achievement (Ladd, Buhs, & Seid, 2000;Strolin-Goltzman et al, 2014), more participation in school (Ladd, Buhs, & Seid, 2000), lower levels of depression and suicidal behaviour (Eisenberg & Resnick, 2006;Galliher, Rostosky, & Hughes, 2004;, and fewer problems with substance abuse (Dornbusch et al, 2001;Henry & Slater, 2007). Conversely, weaker feelings of school attachment have been associated with higher levels of misconduct at school (Henry & Huizinga, 2007;Hirschfield & Gasper, 2011), lower academic achievement, skipping school, and dropping out of school (Henry, Knight, & Thornberry, 2012;Hirschfield & Gasper, 2011).…”
mentioning
confidence: 99%